Carbodiimide‐Induced Formation of Transient Polyether Cages. Issue 6 (17th October 2022) - Hossain, Mohammad Mosharraf; Jayalath, Isuru M.; Baral, Renuka; Hartley, C. Scott
Abstract: The front cover artwork is provided by the Hartley group at Miami University. The image shows a cartoon of transient molecular cages generated through the action of a chemical fuel on macrocycles with pendant groups. The cages are able to bind ions. Read the full text of the Research Article at 10.1002/syst.202200016 . Abstract : "Chemical systems out of equilibrium respond differently to their environments compared to analogous systems at equilibrium. In this work, transient crown‐ether cages were generated using a carbodiimide "fuel". The cages exhibit unusual templation effects: negative templation in the presence of some alkali metal cations, positive templation with others…" This and more about the story behind the front cover can be found in the Research Article at 10.1002/syst.202200016 .